Integration of Differential Equations by <semantics>C∞</semantics>-Structures - Antonio Jesús Pan-Collantes; Concepción Muriel; Adrián Ruiz (Mathematics, 2023)
Several integrability problems of differential equations are addressed using the concept of a <semantics>C∞</semantics>-structure, a recent generalization of the notion of solvable structure. Specifically, the integration procedure associated with <semantics>C∞</semantics>-structures is used to integrate a Lotka–Volterra model and several differential equations that lack sufficient Lie point symmetries and cannot be solved using conventional methods.